2023
DOI: 10.1002/adfm.202308507
|View full text |Cite
|
Sign up to set email alerts
|

A Graphdiyne Nanoreactor for Conversion of NO3 to NH3 from Wastewater

Shuya Zhao,
Zhaoyang Chen,
Zhiqiang Zheng
et al.

Abstract: The lack of highly active and selective catalysts is a major obstacle to replace traditional Haber–Bosch process for electrocatalytic production of ammonia (NH3) at ambient conditions. A new hollow graphdiyne nanoreactor (GDYNR) is reported to overcome this issue effectively. The GDYNR is synthesized by in situ growth of GDY on the inner and outer surfaces of the cobalt hydroxide sphere to form a high‐performance interface structure. Experimental results demonstrate that the incomplete charge transfer between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In general, the Cu nanowires array was prepared through electrochemical anodization of Cu foam followed by a chemical reduction procedure, and then the cross-coupling reaction of HEB occurred on as-prepared Cu nanowires to form a Cu@GDY heterostructure. It is also important to realize the precisely controlled construction of GDY/nanoparticles heterostructured catalysts with highly active heterogeneous interfaces, which has drawn increasing attention from researchers. Li et al reported the GDY@Janus magnetite heterostructure with excellent performance for photocatalytic nitrogen fixation . In their work, GDY was used as the substrate to absorb Fe 2+ ions, followed by a nucleation and growth process of FeO x nanoparticles, in which GDY played an important role to change the morphology, coordination environment, and valence states of FeO x .…”
Section: Controlled Synthesis Of Graphdiyne-based Multiscale Catalystsmentioning
confidence: 99%
“…In general, the Cu nanowires array was prepared through electrochemical anodization of Cu foam followed by a chemical reduction procedure, and then the cross-coupling reaction of HEB occurred on as-prepared Cu nanowires to form a Cu@GDY heterostructure. It is also important to realize the precisely controlled construction of GDY/nanoparticles heterostructured catalysts with highly active heterogeneous interfaces, which has drawn increasing attention from researchers. Li et al reported the GDY@Janus magnetite heterostructure with excellent performance for photocatalytic nitrogen fixation . In their work, GDY was used as the substrate to absorb Fe 2+ ions, followed by a nucleation and growth process of FeO x nanoparticles, in which GDY played an important role to change the morphology, coordination environment, and valence states of FeO x .…”
Section: Controlled Synthesis Of Graphdiyne-based Multiscale Catalystsmentioning
confidence: 99%
“…Incorporating metal catalysts with carbon materials has been considered as an effective way to maximize the number of the active sites, improve the intrinsic activity, and achieve high-performance catalysts. As a rising star of carbon material, graphdiyne (GDY) shows great application value in catalysis field due to its promising and distinctive properties, including the unique sp/sp 2 cohybridized all-carbon network, natural pores, natural band gap, superlarge π structures, abundant carbon chemical bonds, unevenly distributed surface charge, and high intrinsic activity, etc. Remarkably, the unique noninteger charge transfer between GDY and metal atoms can effectively regulate the electronic structure of active sites, promoting the adsorption and conversion of NO 3 – , resistance to intermediate toxicity, and selective N–H coupling. These unique advantages of GDY make it an ideal platform for the construction of new catalysts to realize the highly efficient reduction of nitrate to NH 3 .…”
mentioning
confidence: 99%
“…These results significantly deviate from the typical alloy structure, which is predominantly composed of zerovalent metal. The strong interactions between GDY and PtCu x QDs induce the formation of mixed valent metal atoms, thereby endowing high catalytic activity upon the catalyst. , …”
mentioning
confidence: 99%
See 1 more Smart Citation